Formaldehyde-free A-grade non-combustible water-based paint and preparation method thereof
By compounding boron-silicon synergistically modified waterborne polyurethane and phosphorus-nitrogen dual-cured waterborne epoxy acrylate, a dual flame retardant mechanism and dense coating are constructed, which solves the problems of formaldehyde residue, low flame retardant grade and imbalance between flexibility and hardness of waterborne coatings, and realizes a highly environmentally friendly, highly flame retardant and comprehensive performance coating.
Patent Information
- Application Number
- CN202511046744.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-09-12
AI Technical Summary
Existing water-based paints have problems such as formaldehyde residual risk, low flame retardancy, and a single film-forming substance leading to an imbalance in flexibility and hardness. They are difficult to meet Class A non-flammable standards and comprehensive performance requirements.
A composite system of boron-silicon synergistically modified waterborne polyurethane and phosphorus-nitrogen dual-cured waterborne epoxy acrylate is adopted. A boron-silicon flame retardant network is constructed through triethyl borate and γ-aminopropyltriethoxysilane. Ammonium hypophosphite and melamine formaldehyde resin generate a phosphorus-oxygen bond cross-linking structure to form a dual flame retardant mechanism. Fillers such as nano-aluminum hydroxide and kaolin are combined to improve the density of the coating.
It has achieved formaldehyde-free, Class A non-flammable, low VOC content, strong adhesion and good durability of water-based paint, which can adapt to long-term decoration and protection functions in complex environments.
Smart Images

Figure BDA0005521957060000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional polymer materials, and in particular to a formaldehyde-free, Class A, non-flammable water-based paint and a preparation method thereof. Background Art
[0002] As an important part of the indoor environment, the environmental friendliness and safety of building decoration materials directly affect the health of residents. Traditional building coatings are mostly solvent-based, which release a large amount of harmful substances such as volatile organic compounds (VOCs) and formaldehyde during production and construction. Long-term exposure may cause respiratory diseases, allergic reactions, and even more serious health problems. With the improvement of environmental awareness, water-based paints have gradually become mainstream due to their advantages such as using water as a dispersion medium and low VOC content. However, existing technologies still have obvious shortcomings: some products still illegally add a small amount of organic solvents to reduce costs or improve certain performance, resulting in the risk of formaldehyde residues not being completely eliminated; more importantly, most water-based paints have insufficient flame retardant properties and cannot meet the strict requirements for high fire protection levels in scenarios such as public buildings and high-rise residential buildings.
[0003] The flame retardant performance defects of water-based coatings are mainly due to the limitations of the flame retardant system. Traditional flame retardant technologies mostly rely on additive flame retardants, such as halogen-based (containing chlorine and bromine) and phosphorus-based (phosphorus compounds). Although halogen-based flame retardants can inhibit combustion through gas phase dilution, they are easily decomposed at high temperatures to produce toxic hydrogen halide gas, which increases the toxicity of smoke; although phosphorus-based flame retardants are less toxic, they have migration and loss problems, and the flame retardant effect of the coating will be significantly reduced after long-term use. In addition, the addition of a single flame retardant often leads to a decrease in physical properties such as coating hardness and adhesion, making it difficult to balance environmental protection and functional requirements, which limits the application of water-based coatings in projects that require Class A non-combustible standards.
[0004] The single nature of the film-forming substance further exacerbates the performance bottleneck of traditional water-based paints. Currently, most products on the market use single resins such as acrylates and polyurethanes as the main film-forming components. Although these resins have good film-forming properties, their functions are relatively simple: although polyurethane has good flexibility, it lacks weather resistance and is prone to yellowing and powdering due to ultraviolet radiation; although acrylates have high hardness, they are brittle and prone to cracking. A single resin system is difficult to simultaneously meet multiple requirements such as "high environmental protection, Class A non-flammability, and durability." Especially in complex environments such as humidity and high temperatures, the coating is prone to shedding and failure due to the release of internal stress, and cannot provide long-term and effective decorative and protective functions for buildings. Therefore, the development of a water-based paint that is both environmentally friendly, highly flame-retardant, and has excellent comprehensive performance has become an urgent problem to be solved in the field of building decoration materials. Summary of the Invention
[0005] The purpose of the present invention is to provide a formaldehyde-free Class A non-flammable water-based paint and a preparation method thereof, which solves the problems of existing water-based paints such as formaldehyde residual risk, low flame retardancy, and imbalance between flexibility and hardness caused by a single film-forming material.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A formaldehyde-free, Class A, non-flammable water-based paint comprising the following raw materials in parts by weight:
[0008] Boron-silicon synergistically modified waterborne polyurethane: 150-250 parts by weight;
[0009] Phosphorus-nitrogen dual-curing waterborne epoxy acrylate: 80-150 parts by weight;
[0010] Deionized water: 250-350 parts by weight;
[0011] Propylene glycol butyl ether: 20-40 parts by weight;
[0012] Nano-aluminum hydroxide: 50-80 parts by weight;
[0013] Kaolin: 30-50 parts by weight;
[0014] Dispersant: 10-20 parts by weight;
[0015] Defoaming agent: 1-3 parts by weight;
[0016] Thickener: 3-6 parts by weight;
[0017] Leveling agent: 2-4 parts by weight;
[0018] Preservative: 0.5-1 parts by weight;
[0019] The preparation method of the boron-silicon synergistically modified waterborne polyurethane comprises the following steps: A1, adding polycarbonate diol and dicyclohexylmethane diisocyanate to a reactor equipped with an agitator, a thermometer, and a nitrogen protection device, reacting at 65-75° C. to generate an isocyanate-terminated waterborne polyurethane prepolymer; then cooling to 45-55° C., sequentially adding methyldiethanolamine, triethyl borate, and γ-aminopropyltriethoxysilane, and continuously stirring the reaction until the pH value of the system stabilizes at 7-8; A2, adding deionized water for high-speed dispersion.
[0020] According to a preferred embodiment of the present invention, the polycarbonate diol was purchased from Wanhua Chemical (Yantai) Co., Ltd., model PCDL 2000 (molecular weight 2000).
[0021] According to a preferred embodiment of the present invention, the dicyclohexylmethane diisocyanate was purchased from Wanhua Chemical (Ningbo) Co., Ltd., model HMDI 500.
[0022] According to a preferred embodiment of the present invention, the methyldiethanolamine is purchased from Jiangsu Feixiang Chemical Co., Ltd. and the model is industrial grade MDEA-200.
[0023] According to a preferred embodiment of the present invention, the triethyl borate is purchased from Chengdu Runxing Disinfection Pharmaceutical Co., Ltd. and is industrial grade triethyl borate (purity ≥98%).
[0024] According to a preferred embodiment of the present invention, the γ-aminopropyltriethoxysilane is purchased from Nanjing Shuguang Chemical Group Co., Ltd., and the model number is KH-550 (industrial grade).
[0025] According to a preferred embodiment of the present invention, the deionized water is purchased from an enterprise-made ultrapure water treatment system, and the conductivity is ≤10 μS / cm.
[0026] According to a preferred embodiment of the present invention, the propylene glycol butyl ether is purchased from Jiangsu Yida Chemical Co., Ltd., and the model is industrial grade PGMS-100.
[0027] According to a preferred embodiment of the present invention, the nano aluminum hydroxide is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. and the model is nano aluminum hydroxide (particle size 50-100 nm).
[0028] According to a preferred embodiment of the present invention, the kaolin is purchased from Guangdong Maoming Kaolin Technology Co., Ltd., and the model is 1250 mesh kaolin (whiteness ≥ 90%).
[0029] According to a preferred embodiment of the present invention, the dispersant was purchased from Wanhua Chemical (Guangdong) Co., Ltd., model 190 (domestic industrial grade).
[0030] According to a preferred embodiment of the present invention, the defoaming agent is purchased from Jiangsu Sixin Technology Application Research Institute Co., Ltd., and the model is silicone defoaming agent DS-800.
[0031] According to a preferred embodiment of the present invention, the thickener is purchased from Shanghai Changfeng Chemical Factory, and the model is hydroxyethyl cellulose HEC-250 (industrial grade).
[0032] According to a preferred embodiment of the present invention, the leveling agent is purchased from Shenzhen Haichuan Chemical Technology Co., Ltd., and the model is acrylic leveling agent. 245.
[0033] According to a preferred embodiment of the present invention, the preservative is purchased from Jiangsu Hengsheng Technology Co., Ltd., and the model is BIT preservative BIT-20 (industrial grade).
[0034] In the preparation process of the boron-silicon synergistically modified waterborne polyurethane of the present invention, a polymerization reaction occurs initially between polycarbonate diol and dicyclohexylmethane diisocyanate under nitrogen protection. The isocyanate groups of dicyclohexylmethane diisocyanate react with the hydroxyl groups of the polycarbonate diol to form a prepolymer containing terminal isocyanate groups. This step, by controlling the reaction temperature and time, ensures the proper exposure of the isocyanate groups, providing active sites for subsequent modification. The temperature is then lowered and methyldiethanolamine is added. Its amino groups react with the remaining isocyanate groups, neutralizing the acidity of the system and introducing hydrophilic groups, making the prepolymer water-dispersible. Triethyl borate and γ-aminopropyltriethoxysilane are then added. The borate groups of triethyl borate coordinate with the hydroxyl or amino groups in the system, forming a stable boron-oxygen bond network. The siloxane groups of γ-aminopropyltriethoxysilane then undergo hydrolysis and condensation with the hydroxyl groups on the polyurethane chains, forming a cross-linked structure connected by siloxane bonds. The introduction of these two types of modifiers not only improves the stability of the system, but also constructs a boron-silicon synergistic flame retardant network, laying the foundation for subsequent flame retardant properties.
[0035] According to a preferred embodiment of the present invention, in step A1, the molar ratio of polycarbonate diol to dicyclohexylmethane diisocyanate is 1:(1.4-1.6); the reaction time at 65-75° C. is 2.5-3 h; and the reaction time with continuous stirring is 1-1.5 h.
[0036] According to a preferred embodiment of the present invention, in step A2, the rotation speed of high-speed dispersion is 1000-1500 rpm, and the time is 10 minutes.
[0037] According to a preferred embodiment of the present invention, the preparation method of the phosphorus-nitrogen dual-curing waterborne epoxy acrylate includes: B1, adding the molar ratio of epoxy resin and acrylic acid into a reactor, and reacting at 85-95°C to obtain a prepolymer; B2, then cooling to 55-65°C, adding ammonium hypophosphite and melamine formaldehyde resin, and simultaneously adding N,N-dimethylbenzylamine dropwise to react.
[0038] According to a preferred embodiment of the present invention, the epoxy resin was purchased from Wanhua Chemical (Yantai) Co., Ltd., model E-51 (bisphenol A type, epoxy value 0.48-0.52 mol / 100g).
[0039] According to a preferred embodiment of the present invention, the acrylic acid is purchased from Wanhua Chemical (Ningbo) Co., Ltd. and is industrial grade acrylic acid (AA, purity ≥99.5%).
[0040] According to a preferred embodiment of the present invention, the ammonium hypophosphite is purchased from Jiangsu Tianyuan Industry and Trade Co., Ltd. and is industrial grade ammonium hypophosphite (purity ≥98%).
[0041] According to a preferred embodiment of the present invention, the melamine formaldehyde resin is purchased from Shandong Shiyuan Chemical Co., Ltd., and the model is MT-100 (solid content ≥95%).
[0042] According to a preferred embodiment of the present invention, the N,N-dimethylbenzylamine is purchased from Jiangsu Feixiang Chemical Co., Ltd. and is industrial grade N,N-dimethylbenzylamine (purity ≥99%).
[0043] During the preparation of the phosphorus-nitrogen dual-cured waterborne epoxy acrylate of the present invention, during the initial reaction between the epoxy resin and acrylic acid, the epoxy groups of the epoxy resin undergo ring-opening addition with the carboxyl groups of the acrylic acid, forming an epoxy-containing acrylate prepolymer. This step, by controlling the molar ratio of epoxy to carboxyl groups, ensures that a certain amount of active epoxy groups remain in the prepolymer, providing reaction sites for subsequent curing. The temperature is then lowered and ammonium hypophosphite and melamine-formaldehyde resin are added. The phosphorus hydroxyl groups of the ammonium hypophosphite react with the remaining epoxy groups in the prepolymer, forming a cross-linked structure connected by phosphorus-oxygen bonds. The amino groups of the melamine-formaldehyde resin then undergo ring-opening addition with the epoxy groups, forming an amino-based cross-linked network. Simultaneously, a small amount of catalyst promotes the reaction of the two curing agents, significantly increasing the cross-linking density of the epoxy groups. These two curing agents, through the synergistic effects of their phosphorus and nitrogen groups, respectively, exert a dual flame-retardant effect of "polyphosphoric acid barrier" and "nitrogen dilution" when the coating is heated, effectively suppressing the combustion reaction.
[0044] According to a preferred embodiment of the present invention, in step B1, the molar ratio of epoxy resin to acrylic acid is 1:(1.1-1.3); and the reaction time at 85-95° C. is 3.5-4 h.
[0045] According to a preferred embodiment of the present invention, in step B2, ammonium hypophosphite accounts for 4-6% of the total mass of the prepolymer; melamine formaldehyde resin accounts for 2-4% of the total mass of the prepolymer; N,N-dimethylbenzylamine accounts for 0.2-0.4% of the total mass of the EA prepolymer; and the reaction time is 1.5-2h.
[0046] The present invention also provides a method for preparing the formaldehyde-free Class A non-flammable water-based paint, comprising the following steps:
[0047] S1, mixing boron-silicon synergistically modified waterborne polyurethane and phosphorus-nitrogen dual-curing waterborne epoxy acrylate, and adding deionized water to dilute;
[0048] S2. Add dispersant, defoamer, nano aluminum hydroxide, kaolin, propylene glycol butyl ether, thickener, leveling agent and preservative in sequence and disperse at high speed;
[0049] S3. Adjust the viscosity to 40-60KU and filter.
[0050] According to a preferred embodiment of the present invention, in step S1, the mass ratio of the boron-silicon synergistically modified waterborne polyurethane to the phosphorus-nitrogen dual-cured waterborne epoxy acrylate is (2-4):1.
[0051] According to a preferred embodiment of the present invention, in step S2, the rotation speed of high-speed dispersion is 800-1200 rpm, and the time is 30-40 minutes.
[0052] According to a preferred embodiment of the present invention, in step S3, the pore size of the filter screen is 100-105 mesh.
[0053] During the overall preparation process of the coating of the present invention, after the two modifiers are mixed and diluted in proportion, the flexible polyurethane segments of the boron-silicon synergistically modified waterborne polyurethane and the rigid epoxy segments of the phosphorus-nitrogen dual-cured waterborne epoxy acrylate in the system are entangled with each other to form a "rigid and flexible" film-forming body. Fillers such as nano-aluminum hydroxide and kaolin are uniformly dispersed in the continuous phase under the action of the dispersant, filling the gaps between the segments and improving the density of the coating; the defoamer eliminates bubbles generated during the production process to avoid pinhole defects in the coating; the thickener adjusts the viscosity of the system to prevent pigment sedimentation and improve the construction performance; the leveling agent reduces the surface tension to form a flat and smooth surface after the coating dries; the preservative inhibits the reproduction of microorganisms in the wet film and extends the storage life of the coating. The synergistic effect of each component ultimately forms a formaldehyde-free, Class A non-flammable waterborne coating with excellent comprehensive performance.
[0054] The beneficial effects of the present invention are:
[0055] The technical effects of the present invention are mainly reflected in the significant improvement of environmental protection performance, flame retardant performance and comprehensive film-forming performance, which effectively solves the dual pain points of traditional water-based coatings in terms of safety and function. In terms of environmental protection performance, the coating completely eliminates the residual harmful substances such as formaldehyde through the collaborative design of two modified compounds. Boron-silicon synergistically modified water-based polyurethane uses polycarbonate diol and dicyclohexylmethane diisocyanate as raw materials. No formaldehyde is added during the reaction process, and the subsequently introduced triethyl borate and γ-aminopropyltriethoxysilane are both environmentally friendly modifiers; phosphorus-nitrogen dual-curing water-based epoxy acrylate uses epoxy resin and acrylic acid as the base, and modified components such as ammonium hypophosphite and melamine formaldehyde resin also do not release volatile harmful substances. The final coating has an extremely low VOC content, which is far below the environmental protection standard for interior decoration materials. Long-term use will not cause respiratory discomfort or allergic reactions due to solvent volatilization, providing a "zero formaldehyde" health guarantee for the indoor environment.
[0056] In terms of flame retardancy, the synergistic effect of the two modifiers enables the coating to meet Class A non-flammability standards. In the boron-silicon synergistically modified waterborne polyurethane, triethyl borate decomposes at high temperatures to form a B2O3 glass-like barrier layer, effectively blocking oxygen and heat transfer. In the phosphorus-nitrogen dual-cured waterborne epoxy acrylate, ammonium hypophosphite decomposes upon heat to form polyphosphoric acid, forming an insulating layer, while melamine formaldehyde resin decomposes to release nitrogen to dilute the flammable gases. These two components work together to create a dual flame retardant mechanism of "barrier + dilution." This dual protection makes the coating less susceptible to combustion when exposed to open flames and prevents the production of toxic fumes, significantly enhancing the safety level of building decoration materials.
[0057] In terms of comprehensive film-forming properties, the complementary characteristics of the two modifiers significantly enhance the durability of the coating. The polyurethane segments of the boron-silicon synergistically modified waterborne polyurethane give the coating excellent flexibility and adhesion, allowing it to adapt to slight deformations of the wall without cracking; the epoxy segments of the phosphorus-nitrogen dual-cured waterborne epoxy acrylate improve the hardness and weather resistance of the coating, effectively resisting yellowing and powdering caused by ultraviolet radiation. In addition, the addition of nano-aluminum hydroxide and kaolin further optimizes the density of the coating, and the synergistic effect of additives such as dispersants and thickeners ensures the stability of construction. The final coating not only has strong adhesion and high scrub resistance, but also can maintain its decorative effect for a long time in complex environments such as humidity and high temperature, providing long-lasting functionality and aesthetics for the building. DETAILED DESCRIPTION
[0058] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content.
[0059] Example 1
[0060] Preparation of boron-silicon synergistic modified waterborne polyurethane: 1000 g of polycarbonate diol (PCDL, molecular weight 2000) and 730 g of dicyclohexylmethane diisocyanate (HMDI, molecular weight 262) were added to a reactor, and a stirrer, thermometer, and nitrogen protection device were installed. Stirring was started and nitrogen was introduced to remove air. The reaction was continued at 68°C with stirring for 2.8 hours to generate an isocyanate-terminated waterborne polyurethane prepolymer. The temperature was then lowered to 50°C, and methyldiethanolamine (MDI) was added to the reactor in sequence. DEA (molecular weight 119), triethyl borate (BTE, molecular weight 145), and γ-aminopropyltriethoxysilane (γ-APS, molecular weight 223) (50 g) were added and stirred until the pH value of the system stabilized at 7.5 (detected by pH test paper). After the pH adjustment was completed, 2000 g of deionized water was added to the reactor, and the high-speed dispersion mode was turned on. Dispersion was continued at a speed of 1200 rpm for 10 minutes to obtain a uniform and stable boron-silicon synergistically modified waterborne polyurethane.
[0061] Preparation of phosphorus-nitrogen dual-cured waterborne epoxy acrylate: 500 g of epoxy resin (E-51, molecular weight 4000) and 600 g of acrylic acid (AA, molecular weight 72) were added to another reactor, which was also equipped with an agitator and thermometer. Stirring and heating were started at 88°C, and the reaction was continued for 3.6 hours to allow the epoxy groups and acrylic acid to fully react to form a prepolymer. After the reaction was completed, the temperature was lowered to 60°C, and 55 g of ammonium hypophosphite, 33 g of melamine formaldehyde resin, and 3.3 g of N,N-dimethylbenzylamine were added to the reactor. The stirring was maintained and the reaction was continued for 1.8 hours to complete the phosphorus-nitrogen dual-cured modification and obtain phosphorus-nitrogen dual-cured waterborne epoxy acrylate.
[0062] Preparation of formaldehyde-free Class A non-flammable water-based coating: 200 g of the boron-silicon synergistically modified water-based polyurethane prepared above and 100 g of phosphorus-nitrogen dual-cured water-based epoxy acrylate were added to a mixing container and stirred at a low speed (300 rpm) to mix evenly; 150 g of deionized water was then added to the mixing container for dilution while maintaining the stirring state; a dispersant (polycarboxylate, 15 g), a defoamer (organic silicon, 2 g), and nano-aluminum hydroxide (particle size 50-100 nm, 6 0g), kaolin (particle size 800-1200 mesh, 40g), propylene glycol butyl ether (30g), thickener (hydroxyethyl cellulose, 4g), leveling agent (silicone, 3g) and preservative (BIT, 0.8g), stirring for 3 minutes after each addition of raw materials to ensure uniform dispersion; finally, the stirring speed is increased to 1000rpm, and dispersion is continued for 35 minutes; after dispersion is completed, the undispersed particles are removed by filtration with a 100-mesh sieve to obtain a formaldehyde-free Class A non-flammable water-based paint.
[0063] Example 2
[0064] The specific preparation method is the same as that in Example 1, except that the boron-silicon synergistically modified waterborne polyurethane is prepared as follows: 1200 g of PCDL and 670 g of HMDI (molar ratio of 1:1.4) are added to a reactor and stirred at 70° C. for 2.6 hours to generate an isocyanate-terminated prepolymer; the temperature is lowered to 48° C., 60 g of MDEA, 25 g of BTE, and 35 g of γ-APS are added, and the mixture is stirred until the pH reaches 7.2; 2200 g of deionized water is added, and the mixture is dispersed at 1100 rpm for 10 minutes. Preparation of phosphorus-nitrogen dual-curing waterborne epoxy acrylate: 600g of E-51 and 550g of AA (molar ratio 1:1.1) were added to a reactor and reacted at 86°C for 3.5 hours. The temperature was then lowered to 58°C, and ammonium hypophosphite (5%, i.e. 55g), melamine formaldehyde resin (2.5%, i.e. 27.5g), and N,N-dimethylbenzylamine (0.25%, i.e. 2.75g) were added and reacted for 1.7 hours. Coating preparation: 300g of boron-silicon modified polyurethane was mixed with 100g of phosphorus-nitrogen epoxy acrylate and diluted with 180g of water. The mixture was then added with 20g of dispersant, 2.5g of defoamer, 70g of nano-aluminum hydroxide, 45g of kaolin, 35g of propylene glycol butyl ether, 5g of thickener, 3.5g of leveling agent, and 1g of preservative. The mixture was dispersed at 1100rpm for 38 minutes, adjusting the viscosity to 55KU, and filtered through a 105-mesh filter.
[0065] Example 3
[0066] The specific preparation method is the same as Example 1, except that for the boron-silicon synergistically modified waterborne polyurethane, 800g of PCDL and 530g of HMDI were added to a reactor and reacted at 72°C for 3 hours to form a prepolymer. The mixture was cooled to 52°C, and 40g of MDEA, 20g of BTE, and 30g of γ-APS were added, stirring until the pH reached 7.8. 1800g of deionized water was added and the mixture was dispersed at 1300 rpm for 10 minutes. For the phosphorus-nitrogen dual-cured waterborne epoxy acrylate, 400g of E-51 and 520g of AA (molar ratio of 1:1.3) were added to a reactor and reacted at 90°C for 4 hours. The mixture was cooled to 62°C, and ammonium hypophosphite (6%, i.e., 50g), melamine formaldehyde resin (4%, i.e., 40g), and N,N-dimethylbenzylamine (0.4%, i.e., 4g) were added and reacted for 2 hours. Preparation of coating: Mix 200g of boron-silicon modified polyurethane with 150g of phosphorus-nitrogen epoxy acrylate, dilute with 200g of water; add 10g of dispersant, 1.5g of defoamer, 50g of nano-aluminum hydroxide, 30g of kaolin, 25g of propylene glycol butyl ether, 3g of thickener, 2g of leveling agent, and 0.5g of preservative, disperse at 900rpm for 32min, adjust the viscosity to 45KU, and filter through 100 mesh.
[0067] Comparative Example 1
[0068] The specific preparation method is the same as that in Example 1, except that 200 g of ordinary water-based polyurethane is taken, diluted with 250 g of water, 10 g of dispersant, 1 g of defoamer, 50 g of nano-aluminum hydroxide, 30 g of kaolin, 20 g of propylene glycol butyl ether, 3 g of thickener, 2 g of leveling agent, and 0.5 g of preservative are added, dispersed at 800 rpm for 30 min, and filtered.
[0069] Comparative Example 2
[0070] The specific preparation method is the same as that in Example 1, except that 150 g of ordinary epoxy acrylate is taken, diluted with 200 g of water, 10 g of dispersant, 1 g of defoamer, 50 g of nano-aluminum hydroxide, 30 g of kaolin, 20 g of propylene glycol butyl ether, 3 g of thickener, 2 g of leveling agent, and 0.5 g of preservative are added, dispersed at 800 rpm for 30 min, and filtered.
[0071] Comparative Example 3
[0072] The specific preparation method is the same as that in Example 1, 200 g of ordinary water-based resin is taken, diluted with 250 g of water, 10 g of dispersant, 1 g of defoamer, 50 g of nano-aluminum hydroxide, 30 g of kaolin, 20 g of propylene glycol butyl ether, 3 g of thickener, 2 g of leveling agent, and 0.5 g of preservative are added, dispersed at 800 rpm for 30 min, and filtered.
[0073] Performance Testing
[0074] The materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance according to the following method:
[0075] 1. VOC content test: According to the "Determination of Volatile Organic Compounds (VOC)" method in GB 18582-2020 "Limits of Hazardous Substances in Building Wall Coatings", take 2 g of the paint sample, add 20 mL of butyl acetate, and ultrasonically extract for 30 minutes. After filtering, the filtrate is detected by gas chromatograph (GC-2010 Plus, Shimadzu). The external standard method is used for quantification, and the VOC content (unit: g / L) is calculated.
[0076] 2. Combustion performance test: According to the "Combustion performance test method for flat building materials and products" in GB 8624-2012 "Classification of combustion performance of building materials and products", the coating is applied to the surface of a 50mm×50mm×3mm inorganic cementitious material plate (dry film thickness 0.3mm), placed in a combustion test furnace, and burned under a flame of (600±20)℃ for 30 minutes. Observe whether it continues to burn, the length of carbonization, and whether there is any dripping that ignites the cotton, and determine the combustion grade (Grade A: non-combustible; Grade B1: difficult to burn; Grade B2: combustible).
[0077] 3. Adhesion Test: According to the "cross-hatch method" test in GB / T 9755-2014 "Synthetic Resin Emulsion Exterior Wall Paint", apply the paint to a tinplate (250mm×150mm×0.3mm). After drying for 7 days, use a cross-hatch cutter (1mm spacing) to make a grid. After taping, remove the tape and observe the grid shedding. Calculate the percentage of shedding area (Level 0: no shedding; Level 1: ≤5% shedding; ≥Level 2: >5% shedding).
[0078] 4. Scrub resistance test: According to the "Scrub resistance test method" in GB / T 9755-2014, the coating was applied to an asbestos cement board (200mm×150mm×3mm). After drying for 7 days, the coating was scrubbed with a scrubber (the scrubbing medium is a 0.5% neutral detergent aqueous solution) at a speed of (370±10) times / min. The number of times the coating was scrubbed until the bottom was exposed was recorded (unit: times).
[0079] 5. Viscosity test: According to the "Determination of Viscosity" method in GB / T 9755-2014, take a coating sample and place it in an NDJ-8S rotational viscometer (rotor model S63). Under constant temperature conditions of 25°C and a rotation speed of (6 rpm), measure the viscosity value (unit: KU).
[0080] 6. Particle size distribution test: Take a coating sample and dilute it 10 times with deionized water. Measure it with a laser particle size analyzer (Malvern Mastersizer 3000) at 25°C and calculate the D90 particle size (90% particle diameter ≤ this value, unit: μm).
[0081] 7. Performance test results:
[0082] Table 1: Performance test results of various embodiments and comparative examples
[0083]
[0084] As can be seen from Table 1, the performance comparison of embodiment 1-3 and comparative example 1-3 clearly shows that the present invention, by the composite system of boron-silicon collaborative modified waterborne polyurethane and phosphorus-nitrogen dual-curing waterborne epoxy acrylate, effectively solves the core problem of existing water-based coatings. From the VOC content, the VOC of embodiment 1-3 is only 2.8-3.5g / L, and no formaldehyde remains, and the VOC of comparative example 1-3 is up to 55.1-62.3g / L, shows that the present invention thoroughly eliminates the harmful substance risks such as formaldehyde. Aspect flame retardant performance, the combustion grade of embodiment 1-3 is all A grade (non-combustible), and comparative example 1-3 is only B1 or B2 grade (combustible or difficult to burn), illustrates that the present invention has significantly improved flame retardant grade by boron-silicon collaborative flame retardant and phosphorus-nitrogen dual-effect curing mechanism. In terms of film-forming performance, the adhesion of Examples 1-3 was all level 0 (no shedding), the scrubbing resistance was ≥12,500 times, and the viscosity was stable (48-55 KU) and the particle size was uniform (28-32 μm). This shows that the flexibility of the boron-silicon synergistically modified waterborne polyurethane complements the hardness of the phosphorus-nitrogen dual-cured waterborne epoxy acrylate, solving the problem of imbalance between flexibility and hardness caused by a single resin film-forming material. In contrast, Comparative Examples 1-3, due to the use of ordinary waterborne resins or single modification systems, experienced problems such as decreased adhesion (level 1-2 shedding), decreased scrubbing resistance (2,500-4,200 times), and viscosity stratification or flocculation (58-70 KU), verifying the comprehensive advantages of the dual-modified resin synergistic system of the present invention.
[0085] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.
Claims
1. A formaldehyde-free, Class A, non-flammable water-based paint, characterized in that: The invention comprises the following raw materials in parts by weight: Boron-silicon synergistically modified waterborne polyurethane: 150-250 parts by weight; Phosphorus-nitrogen dual-curing waterborne epoxy acrylate: 80-150 parts by weight; Deionized water: 250-350 parts by weight; Propylene glycol butyl ether: 20-40 parts by weight; Nano-aluminum hydroxide: 50-80 parts by weight; Kaolin: 30-50 parts by weight; Dispersant: 10-20 parts by weight; Defoaming agent: 1-3 parts by weight; Thickener: 3-6 parts by weight; Leveling agent: 2-4 parts by weight; Preservative: 0.5-1 parts by weight; The preparation method of the boron-silicon synergistically modified waterborne polyurethane comprises the following steps: A1, adding polycarbonate diol and dicyclohexylmethane diisocyanate to a reactor equipped with an agitator, a thermometer, and a nitrogen protection device, reacting at 65-75° C. to generate an isocyanate-terminated waterborne polyurethane prepolymer; then cooling to 45-55° C., sequentially adding methyldiethanolamine, triethyl borate, and γ-aminopropyltriethoxysilane, and continuously stirring the reaction until the pH value of the system stabilizes at 7-8; A2, adding deionized water for high-speed dispersion.
2. The formaldehyde-free Class A non-flammable water-based paint according to claim 1, characterized in that: In step A1, the molar ratio of polycarbonate diol to dicyclohexylmethane diisocyanate is 1:(1.4-1.6); the reaction time at 65-75° C. is 2.5-3 h; and the reaction time with continuous stirring is 1-1.5 h.
3. The formaldehyde-free Class A non-flammable water-based paint according to claim 1, characterized in that: In step A2, the high-speed dispersion speed is 1000-1500 rpm and the time is 10 minutes.
4. The formaldehyde-free, Class A, non-flammable water-based paint according to claim 1, characterized in that: The preparation method of the phosphorus-nitrogen dual-curing waterborne epoxy acrylate comprises: B1, adding epoxy resin and acrylic acid in a molar ratio into a reaction kettle, reacting at 85-95° C. to obtain a prepolymer; B2, subsequently cooling to 55-65° C., adding ammonium hypophosphite and melamine formaldehyde resin, and simultaneously adding N,N-dimethylbenzylamine dropwise for reaction.
5. The formaldehyde-free, Class A, non-flammable water-based paint according to claim 4, characterized in that: In step B1, the molar ratio of epoxy resin to acrylic acid is 1:(1.1-1.3); and the reaction time at 85-95° C. is 3.5-4 h.
6. The formaldehyde-free, Class A, non-flammable water-based paint according to claim 4, characterized in that: In step B2, ammonium hypophosphite accounts for 4-6% of the total mass of the prepolymer; melamine formaldehyde resin accounts for 2-4% of the total mass of the prepolymer; N,N-dimethylbenzylamine accounts for 0.2-0.4% of the total mass of the EA prepolymer; and the reaction time is 1.5-2 hours.
7. A method for preparing a formaldehyde-free, Class A, non-flammable water-based paint according to any one of claims 1 to 6, characterized in that the steps include: S1, mixing boron-silicon synergistically modified waterborne polyurethane and phosphorus-nitrogen dual-curing waterborne epoxy acrylate, and adding deionized water to dilute; S2. Add dispersant, defoamer, nano aluminum hydroxide, kaolin, propylene glycol butyl ether, thickener, leveling agent and preservative in sequence and disperse at high speed; S3. Adjust the viscosity to 40-60KU and filter.
8. The preparation method according to claim 7, characterized in that In step S1, the mass ratio of boron-silicon synergistically modified waterborne polyurethane to phosphorus-nitrogen dual-cured waterborne epoxy acrylate is (2-4):
1.
9. The preparation method according to claim 7, characterized in that In step S2, the speed of high-speed dispersion is 800-1200 rpm, and the time is 30-40 minutes.
10. The preparation method according to claim 7, characterized in that In step S3, the pore size of the filter screen is 100-105 mesh.